2005
DOI: 10.1095/biolreprod.104.036012
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Configuration Within the Germinal Vesicle of Horse Oocytes: Changes Post Mortem and Relationship to Meiotic and Developmental Competence1

Abstract: We evaluated the relationship of initial chromatin configuration to time of oocyte recovery and to nuclear maturation after culture in horse oocytes having compact (Cp) and expanded (Ex) cumuli. In addition, we evaluated the effect of oocyte type, time of recovery, and duration of culture on blastocyst development after intracytoplasmic sperm injection. In oocytes collected within 1 h of slaughter, fibrillar and intermediate chromatin configurations were more prevalent in Cp than in Ex oocytes (68% and 12%, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
131
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(144 citation statements)
references
References 55 publications
10
131
2
1
Order By: Relevance
“…In the present study, we stored equine ovaries at 15 to 20 C and successfully cultured the oocytes to the blastocyst stage (25.5%). Our results were comparable with other recent studies that achieved blastocyst rates of 27-39% after ICSI using ovaries preserved for 3-9 h [11][12][13]. These results indicate that the immature horse oocytes from ovaries preserved for one day retained their in vitro developmental competence.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, we stored equine ovaries at 15 to 20 C and successfully cultured the oocytes to the blastocyst stage (25.5%). Our results were comparable with other recent studies that achieved blastocyst rates of 27-39% after ICSI using ovaries preserved for 3-9 h [11][12][13]. These results indicate that the immature horse oocytes from ovaries preserved for one day retained their in vitro developmental competence.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, several studies have shown that blastocyst formation rates of 27-39% can be obtained by in vitro culture (IVC) following ICSI of equine oocytes from ovaries preserved for 3-9 h [11][12][13]. However, up to now, there have been few reports about the effect of storage of ovaries for one day on subsequent embryogenesis in the horse.…”
mentioning
confidence: 99%
“…Horses make a valuable model for oocyte assessments associated with penetration of the zona pellucida (e.g. PB biopsy) because, in contrast to species such as cattle and sheep, methods for fertilization via intracytoplasmic sperm injection (ICSI) are well established in the horse (Hinrichs et al, 2005;Choi et al, 2006). Sperm injection is necessary to achieve fertilization after penetration of the zona pellucida for investigative p u r p o s e s , a s t h e d e f e c t i n t h e z o n a w o u l d l e a d t o p o l y s p e r m y i f s t a n d a r d i n v i t r o fertilization (IVF) were to be performed.…”
Section: The Mare As a Model For Human Oocyte Biologymentioning
confidence: 99%
“…Despite the relatively low per oocyte success rates (18%-36% of recovered oocytes develop into a transferable blastocyst; Hinrichs et al 2005;Galli et al 2007), during the past 5 years IVP has become a commercially viable means of breeding horses. The increasing popularity of IVP despite the relatively high costs is explained by the number of transferable blastocysts per ovum pick-up (OPU) session (0.6-0.8; Galli et al 2014), which compares favourably with embryo flushing in the field.…”
Section: Introductionmentioning
confidence: 99%